Computational Fluid Dynamics Modelling of Flocculation in Water Treatment: A Review - Bridgeman, J.; Jefferson, Bruce; Parsons, Simon A. (Cranfield University, 2009)
The principal focus of this paper is to present a critical review of current approaches to modelling the inter-related hydrodynamic, physical and chemical processes involved in the flocculation of water using Computational Fluid Dynamics (CFD). The flows inside both laboratory and full scale mechanically- mixed flocculators are complex and pose significant challenges to modellers. There exists a body of published work which considers the bulk flow patterns, primarily at laboratory scale. However, there is little reported multiphase modelling at either scale. Two-equation turbulence modelling has been found to produce variable results in comparison with experimental data, due to the anisotropic nature of the swirling flow. However, the computational expense of combining the sliding mesh treatment for a rotating mesh with the Reynolds Stress Model (RSM) in a full scale unit is great, even when using a high performance computing facility. Future work should focus more on the multiphase modelling aspects. Whilst opportunities exist for particle tracking using a Lagrangian model, few workers have attempted this. The fractal nature of flocs poses limitations on the accuracy of the results generated and, in particular, the impacts of density and porosity on drag force and settlement characteristics require additional work. There is significant scope for the use of coupled population balance models and CFD to develop water treatment flocculation models. Results from related work in the wastewater flocculation field are encouraging.
Keywords: computational fluid dynamics; turbulence; flocculation; mixing; multiphase modelling; fractal dimension